FINANCIAL ACCOUNTING INFORMATION SYSTEM AS AN ANALYSIS OF COOPERATIVE PROFIT PLANNING USING THE WEB-BASED COST VOLUME PROFIT (CVP) METHOD (Case Study: at KSPPS Mitra Amanah Sejahtera Abadi, Kendal) - Dewi Retno Putri; Danang Danang (Journal of Engineering, Electrical and Informatics, 2021)
The research was conducted at KSPPS Mitra Amanah Sejahtera Abadi. Which is located at Ds. Sidorejo Rt. 02 / Rw. 05 Kec. Brangsong Kab. Kendal. Data recording and management previously applied to the MASA Cooperative is still manual. Transaction data such as daily dropping, dropping per AO, daily withdrawals and general ledgers and journals will be entered manually into the book. And the resulting data is inaccurate, and there has also been no good profit planning in the cooperative so far, only comparing revenues and expenses and fulfilling cooperative activities, so that the cooperative lacks funds or capital for the following year so it has to hold SHU members from being distributed and used as capital for the following year. To simplify and speed up the transaction process and making reports and planning for cooperative profits, an accounting information system application is made for cooperatives. This is to facilitate the secretary / member in recording and making financial reports and planning the profit of the cooperative, the secretary / member only needs to input the application data once and the report can be directly covered in one application and the secretary / member can print it. This study aims to facilitate the presentation of the profit planning analysis report which is applied to the cooperative each year. The use of bookkeeping that has been applied so far is felt to have several weaknesses which cause several problems. Therefore, cooperatives need to develop a new system, namely a computer-based financial accounting information system.The Cost Volume Profit method is expected to be able to carry out good profit planning and more valid financial records so that it can reduce the risk of errors and the process is much faster.